2010
DOI: 10.1215/00031283-2010-003
|View full text |Cite
|
Sign up to set email alerts
|

MUMBLING IS Macho: PHONETIC DISTINCTIVENESS IN THE SPEECH OF AMERICAN RADIO Djs

Abstract: Phonetic studies of phonological contrasts in features such as vowel height and consonant voicing have revealed a gender difference: phonetic correlates of phonological contrasts produced by women tend to be more distinct in acoustic and temporal space than those produced by men. However, these studies have been constrained by their dichotomous approach to gender. This article examines withinsex variation in phonetic correlates of phonological contrasts among eight American male radio disc jockeys. four variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…It has been suggested that clearer female speech may be a consequence of females often being the primary care-givers and most important initial source of language input for a child (Labov, 1990). In addition, Heffernan (2010) found in his analysis of several parameters of phonetic distinctiveness (such as vowel space dispersion and vowel length contrast) in American male radio disk jockeys a significant correlation between phonetic distinctiveness and perceived masculinity, leading the author to conclude that "mumbling is macho. "…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that clearer female speech may be a consequence of females often being the primary care-givers and most important initial source of language input for a child (Labov, 1990). In addition, Heffernan (2010) found in his analysis of several parameters of phonetic distinctiveness (such as vowel space dispersion and vowel length contrast) in American male radio disk jockeys a significant correlation between phonetic distinctiveness and perceived masculinity, leading the author to conclude that "mumbling is macho. "…”
Section: Introductionmentioning
confidence: 99%
“…The association of certain spectral cues in speech and perceived masculinity has been found before [3943,7375]. Lower fundamental frequency and lower formant values resulting in smaller vowel spaces have been found to correlate with perceived masculinity and thereby increased attractiveness in male voices (e.g.…”
Section: Discussionmentioning
confidence: 74%
“…Lower fundamental frequency and lower formant values resulting in smaller vowel spaces have been found to correlate with perceived masculinity and thereby increased attractiveness in male voices (e.g. [43,75]). As stated before, differences between languages exist regarding the salience of a particular acoustic cue (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreigner-and infant-directed speech has also been shown to sometimes show formant space area expansion (Uther et al, 2007). There also appears to be a relationship between vowel-space dispersion and the perception of indexical characteristics related to speaker gender and sexual orientation (Heffernan, 2010;Munson, 2007). Finally, it has been suggested that some aspects of apparent non-uniform scaling in formant averages between male and female speakers may be due to the fact that in some sociocultural contexts, female speakers may tend to produce "clearer," more dispersed speech (Goldstein, 1980;Diehl et al, 1996).…”
Section: Lobanov Normalization Methods As a Perceptual Modelmentioning
confidence: 99%